Computational characterization of residue couplings and micropolymorphism-induced changes in the dynamics of two differentially disease-associated human MHC class-I alleles - ÖZBEK SARICA, PEMRA (TAYLOR & FRANCIS INC, 2018)
Human major histocompatibility complex class I (MHC I) - or human leukocyte antigen (HLA) - proteins present intracellularly processed peptides to cytotoxic T lymphocytes in the adaptive immune response to pathogens. A high level of polymorphism in human MHC I proteins defines the peptide-binding specificity of thousands of different MHC alleles. However, polymorphism as well as the peptide ligand can also affect the global dynamics of the complex. In this study, we conducted classical molecular dynamics simulations of two HLA alleles, the ankylosing spondylitis (AS) associated/tapasin-dependent HLA-B*27:05 and nondisease-associated/tapasin-independent HLA-B*27:09, both in peptide-free forms as well as complex with four different peptides ligands. Our results indicate that in peptide-free form, the single amino acid substitution distinguishing the two alleles (D116H), leads to a weaker dynamic coupling of residues in the tapasin-dependent HLA-B*27:05. In peptide-bound form, several residues of the binding-groove, mostly in A and B pockets, show hinge-like behavior in the global motion of the MHC. Moreover, allele-dependent changes are shown in residue interactions, affecting the B-pocket as well as the beta-2-microglobulin (2m)-facing residues of the HLA chain.
Keywords: human leukocyte antigens; major histocompatibility complex class I; molecular dynamics; ankylosing spondylitis; Tapasin dependency; HLA-B27; allostery; global dynamics; MOLECULAR-DYNAMICS; HLA-B27 SUBTYPES; PEPTIDE-BINDING; ANKYLOSING-SPONDYLITIS; POCKET FLEXIBILITY; SELECTOR FUNCTION; DISULFIDE BRIDGE; SELF-PEPTIDES; COMPLEX; PROTEIN